Evaluación de 6 portainjertos híbridos para tangor murcott (Citrus reticulata × C. sinensis) - Beltran, Victor Manuel; Torrez, Diomede; Cardozo, Gustavo Daniel; Dominguez, Carlos; Garavello, Miguel Fernando (EEA Concordia, INTA, 2023)
Póster